Measuring the Impacts of Global Trade Reform with Optimal Aggregators of Distortions. Issue 2 (3rd November 2016) - Laborde, David; Martin, Will; van der Mensbrugghe, Dominique
Abstract: Aggregation of trade distortion measures is essential in applied work, but traditional trade‐weighted average measures are egregiously flawed. This paper shows how appropriate tariff aggregation can overcome underestimation of both efficiency and terms‐of‐trade gains from reform. The improvement is shown to result from better measurement of a distortion effect that is most important in the early stages of reform and a weighting effect that becomes more important as protection is reduced. Applications confirm that the technique can be applied relatively easily, and—with elasticity estimates suggested by the available econometric evidence—point to close to a doubling of the global welfare gains from global trade reform, and dramatic changes in the measured welfare impacts in many individual cases. Sensitivity analysis suggests that, for global trade reform, the ease of substitution between tariff lines is much more important than that between varieties from different countries. We provide an online aggregation tool to allow replication of our analysis or investigation of alternative scenarios for global reform. We hope that this paper will contribute both to wider use of optimal aggregators and improved estimates of the key elasticity parameters.